Evaluasi Status Mutu Air Sungai Deli Kota Medan Menggunakan Metode Indeks Pencemaran - Nuriyana, Nuriyana; Gusdini, Ninin; Febriana, Laila (Journal of Natural Sciences, 2026)
The water quality of the Deli River has declined due to pressures from domestic and industrial activities as well as land use changes. This study aims to evaluate the water quality status of the Deli River in Medan City using the Pollution Index (PI) method. The study was conducted in 2024 at two locations (upstream and downstream) during the rainy and dry seasons. Data were obtained through laboratory analysis of physical, chemical, and microbiological parameters based on the water quality standards of Government Regulation No. 22 of 2021. The results showed that most parameters met the quality standards during the rainy season, while increased pollutant concentrations were observed in the dry season, particularly total phosphate (0.92 mg/L) and cadmium (0.02 mg/L), which exceeded the permissible limits. The Pollution Index indicated good water quality during the rainy season (0.370–0.541) and lightly polluted conditions during the dry season (1.833–3.117). The PI values tended to increase from upstream to downstream due to the accumulation of pollutant loads. It can be concluded that the water quality of the Deli River is influenced by seasonal variation and anthropogenic activities, with more degraded conditions occurring during the dry season and in downstream areas.